On The Investıgatıon Of Homonyms From The Structural-Semantıc Poınt Of Vıew In Englısh - Gızı, Bayramlı Aynur Humay (Advances in Social Sciences Research Journal, 2019)
Language is considered to be the main indicator of each nation’s material and spiritual culture. It is directly related to the labor and social activities of people’s. The developing and changing things that are seen in the world are immediately reflected in the language. The lexical layer of the language is constantly increasing and developing; new notions, and new names are need in the language day by day. The word is not considered to be only the source of investigation of linguistics, but also logic, psychology or philosophy. The word is dealt with in linguistics from the point of view of phonetics, lexis, etymology, word building, morphological, syntactical and stylistics. The words as the members of the language system are related to one another. There are also some inner relations among them in the sentences. The words and their meanings are connected in different groups, and these connections base on similarity and meaning. The changing of meanings of words depend on the inner laws of the languages, and the specific features of the language structure. Each language’s dictionary content cover some layers of words relating to homonyms. The homonymy is meant to the a historical category and is considered to play a crucial role in the development of languages. It was derived due to the nature of the language; it has a long way of history and it has its own place in each language. Like the other categories of lexics, the meanings of homonyms which have a very important place in the semantic system of languages, can be clarified inside the sentences, texts, discourses, etc. The difficulties of homonyms are explained due to the fact that they have some similarities with the polysemy. It is a known fact that some homonyms have been derived from the polysemy. This process is observed to be realized relating to the fact that one meanings of the words of polysemy has been developing and being far away from its main meaning and becomes an independent word. The homonyms are used to occupy the places that reject each other. Because of this, the main function of homonyms such as different in meaning but similar in pronunciation are noticed.